The impact of word recognition from speech (WRS) proficiency level on interaction, task success and word learning: design implications for CALL to develop L2 WRS. Issue 1 (17th February 2017) - Matthews, Joshua; O'Toole, John Mitchell; Chen, Shen
Abstract : This paper reports on task interaction, task success and word learning among second language (L2) learners of different levels of word recognition from speech (WRS) proficiency who used a CALL application previously shown to be effective in the development of L2 WRS. Participants ( N = 65) were categorised into three levels of L2 WRS proficiency according to their baseline ability to accurately recognise the phonological form of words in connected speech. All participants undertook the same web-based intervention task which involved reconstructing spoken text into the written form in a number of stages. In terms of task interaction, lower WRS proficiency participants chose to listen to stimulus material more often and changed their efforts at reconstruction significantly more frequently than participants of higher WRS proficiency levels. In relation to task success, lower WRS proficiency learners were significantly less accurate overall and less immediate in their arrival at peak reconstruction accuracy than higher WRS proficiency participants. A comparison of gain scores also showed that participants of different L2 WRS proficiency experienced significantly different word learning outcomes after using the application, with moderate WRS proficiency participants significantly outperforming lower WRS proficiency level learners in relation to academic word learning. A synthesis of the results is used to recommend design features of CALL for WRS development which will more adequately cater to learners of different L2 WRS proficiency levels. The paper concludes with some avenues for future research and some implications for the integration of computer-mediated L2 WRS development as a component of L2 listening instruction.